Conventional and Soft-Computing Based MPPT Methods Comparisons in Direct and Indirect Modes for Single Stage PV Systems - Ekrem Kandemir; Selim Borekci; Numan Sabit Cetin (Elektronika ir Elektrotechnika, 2018)
Improving power efficiency for a Photovoltaic (PV) system becomes important issue for researchers. To achieve maximum power extraction from PV panels, different kinds of Maximum Power Point Tracking (MPPT) methods have been investigating in the literature. In all techniques, direct and indirect mode approaches can be implemented. Based on the physical application of the PV system under different condition, the efficiency and convergence speed become important. In this paper, a grid connected simple single stage PV system by using different MPPT methods in direct and indirect modes has been analysed to find out the best mode and technique for a specific PV system application. Three of the most preferred MPPT algorithms: the perturb & observe (P&O), incremental conductance (Inc. Cond.) and fuzzy logic control (FLC) have been performed in MATLAB Simulink and compared their performance in direct and indirect modes in terms of convergence speed and tracking accuracy by the proposed single stage PV system. The results show that direct mode MPPTs have better tracking accuracy but less convergence speed than indirect MPPTs. Therefore, indirect mode MPPTs present better performance for the rapid atmospheric changing applications. Additionally, FLC based MPPT exhibits almost best tracking performance for direct and indirect modes.